Relationships between feeding and glucose concentrations in healthy term infants during the first five days after birth—the Glucose in Well Babies Study (GLOW) - Harris, Deborah L; Weston, Philip J.; Harding, Jane E (Frontiers in Pediatrics, 2023)
Background The World Health Organization recommends breastfeeding be commenced as soon as possible after birth. Amongst other benefits, early feeding is expected to support the metabolic transition after birth, but effects on blood glucose concentrations are controversial. We sought to describe the changes in interstitial glucose concentrations after feedings over the first five postnatal days. Participants and Methods In healthy singleton term infants, all feeds were recorded using a smart phone app. Glucose concentrations were measured by blinded interstitial monitoring, calibrated by heel-prick capillary samples 2–4 times/d. Feeding sessions were included if a start and end time were recorded, and if the interval between the start of successive feeds was >90 min. The area under the glucose concentration curve (AUC) was calculated by trapezoidal addition from baseline (median of the 3 measurements before the beginning of the session). The maximum deviation (MD) was the greatest change in glucose concentration (positive or negative) from baseline to the next feeding session or 180 min, whichever came first. Data were analyzed using Stata V17 and are presented as mean (95% CI) in mmol/L. Results Data were available for 62 infants and 1,770 feedings. The glucose response to breastfeeding was not different from zero on day 1 [day 1 AUC 0.05 (−0.00, 0.10), MD 0.06 (−0.05, 0.16)], but increased thereafter (day 3 (AUC 0.23 (0.18, 0.28), MD 0.41 (0.32, 0.50), day 5 AUC 0.11 (0.06, 0.16), MD 0.28 (0.18, 0.37), p < 0.001 for age effect). Glucose response increased with increased duration of breastfeeding (<30 min AUC 0.06 (0.02,0.09), MD 0.12 (0.04,0.19), >30 min AUC 0.20 (0.16, 0.23) MD 0.37 (0.30, 0.44), p < 0.001 for duration effect) and this was observed even in the first 2 days (<30 min AUC-0.02 (−0.06, 0.03), MD −0.06 (−0.15, 0.03), >30 min AUC 0.12 (0.08, 0.16), MD 0.19 (0.11, 0.27), overall p < 0.001 for age x duration interaction). In feeding sessions that were not breastfeeding, the glucose response was greater after formula than after expressed human milk [AUC 0.29 (0.15, 0.29), MD 0.48 (−0.12, 0.61)], and greater after feed volumes >20 ml than <10 ml [20–30 ml AUC 0.19 (0.01, 0.27), MD 0.23 (−0.01, 0.46)]. Conclusion The glucose response to feeding in the days after birth increases with postnatal age and duration of the feeding episode. Breastfeeding for <30 min has little effect on glucose concentrations in the first two days.